Where do we want to see other people while relaxing in a city park? Visual relationships with park users and their impact on preferences, safety and privacy. (February 2021) - Lis, Aleksandra; Iwankowski, Paweł
Abstract: Recreation in a public park is associated with contact with other people spending time in a park setting. The choices people make about visiting a park are not always associated with the need for contact. Sometimes privacy and/or safety is more important, and this is related to the presence of other people in the area and where these people are. We examined how our preferences are influenced by how far other people are from us (distance) and to what extent they are visible (obstruction). We also verified whether the reason for these preferences stems from sense of safety and privacy. To this end, we designed a study in which participants rated 112 photos of park settings in terms of perceived safety, privacy and landscape preference. We measured the distances from people in situ . We measured the degree of obstruction in the pictures as the relative (percentage) quantity of landscape forms constituting a visual barrier. Mediation analyses revealed that (1) increasing the distance from other people in a particular area has a positive effect on preferences, caused by increased privacy and safety; (2) obstruction reduces sense of safety, which in turn reduces privacy and, as a result, reduces preferences. These results indicate that people feel safe and well in situations when they see other people in the area and are not separated from them by visual obstruction, as long as these people are located some distance away. That is why it is worth creating spaces for relaxation located away from active spaces but where the active people are clearly visible. Highlights: Landscape preferences increase as the distance from other park visitors increases. Landscape preferences decrease as the quantity of visual barriers increases. Privacy and safety mediate the relationship between preferences and distance. Obstruction correlates positively with privacy if we control for safety. Safety and privacy sequentially mediate the relationship between obstruction and preference.